Murabahah Financing And Its Implementation For the Economic Empowerment of the Ummah - Rahmat, Abdul (IKONOMIKA, 2017)
The discussion in this research is conducted to know the implementation of supervision of shahibul maal done in reducing the financing problem. In accordance with the provisions of Bank Indonesia that the amount of non-performing financing disbursed shall not exceed 5%. While on average per year the number of shahibul maal financing problem is greater than 5%, resulting from 5%. To be able to perform the rescue of troubled financing, some efforts need to be done such as rescheduling to allow leeway to Shahibul Maal to pay the financing that has been due by delaying the maturity date. Then re-arrange the financing requirements to strengthen the bargaining position with the customer by reviewing the contents of the financing agreement when necessary plus or minus. And improve the funding structure (recapitulation) and business organization, help improve the condition and financial liquidity of Shahibul Maal. Thus little by little Shahibul Maal was able to pay off his troubled financing